Identification of candidate gene FAM183A and novel pathogenic variants in known genes: High genetic heterogeneity for autosomal recessive intellectual disability - ELÇİOĞLU, HURİYE NURSEL (PUBLIC LIBRARY SCIENCE, 2018)
The etiology of intellectual disability (ID) is heterogeneous including a variety of genetic and environmental causes. Historically, most research has not focused on autosomal recessive ID (ARID), which is a significant cause of ID, particularly in areas where parental consanguinity is common. Identification of genetic causes allows for precision diagnosis and improved genetic counseling. We performed whole exome sequencing to 21 Turkish families, seven multiplex and 14 simplex, with nonsyndromic ID. Based on the presence of multiple affected siblings born to unaffected parents and/or shared ancestry, we consider all families as ARID. We revealed the underlying causative variants in seven families in MCPH1 (c.427dupA, p.T143Nfs*5), WDR62 (c.3406C>T, p.R1136*), ASPM (c.5219_5225delGAG-GATA, p.R1740Tfs*7), RARS (c.1588A>G, p.T530A), CC2D1A (c.811delG, p.A271Pfs*30), TUSC3 (c.793C>T, p.Q265*) and ZNF335 (c.808C>T, p.R270C and c.3715C>A, p.Q1239K) previously linked with ARID. Besides ARID genes, in one family, affected male siblings were hemizygous for PQBP1 (c.459_462delAGAG, p.R153Sfs*41) and in one family the proband was female and heterozygous for X-chromosomal SLC9A6 (c.1631+1G>A) variant. Each of these variants, except for those in MCPH1 and PQBP1, have not been previously published. Additionally in one family, two affected children were homozygous for the c.377G>A (p.W126*) variant in the FAM183A, a gene not previously associated with ARID. No causative variants were found in the remaining 11 families. A wide variety of variants explain half of families with ARID. FAM183A is a promising novel candidate gene for ARID.
Keywords: COPY-NUMBER VARIATION; MENTAL-RETARDATION; MUTATIONS; WDR62; ASPM; FAMILIES; PROTEIN; SLC9A6; ASSOCIATION; DISCOVERY